2017
DOI: 10.1177/1352458517726593
|View full text |Cite
|
Sign up to set email alerts
|

Endocrinopathies in paediatric-onset neuromyelitis optica spectrum disorder with aquaporin 4 (AQP4) antibody

Abstract: The involvement of the diencephalic regions in neuromyelitis optica spectrum disorder (NMOSD) may lead to endocrinopathies. In this study we identified the following endocrinopathies in 60%(15/25) of young people with paediatric-onset AQP4-Ab NMOSD: morbid obesity (n=8), hyperinsulinaemia (n=5), hyperandrogenism (n=5), amenorrhoea (n=5), hyponatraemia (n=4), short stature (n=3) and central hypothyroidism (n=2) irrespective of hypothalamic lesions. Morbid obesity was seen in 88%(7/8) of children of Caribbean or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…No therapies are currently FDA approved for use in children with NMOSD. Retrospective studies have shown benefit with mycophenolate mofetil (titrated over 3 to 4 weeks to goal dosing of 600 mg/m 2 2 times a day, maximum of 1 g 2 times a day), 73 azathioprine (2 mg/kg/d to 3 mg/kg/d), 78 and rituximab (dosed as noted in table 6-2 ), 74,75 and a small case series supports the use of tocilizumab (8 mg/kg every 4 weeks, maximum of 800 mg per dose) 79 . The author typically avoids azathioprine in children given its higher risk of intolerable side effects.…”
Section: Relapsing Demyelinating Syndromesmentioning
confidence: 93%
See 1 more Smart Citation
“…No therapies are currently FDA approved for use in children with NMOSD. Retrospective studies have shown benefit with mycophenolate mofetil (titrated over 3 to 4 weeks to goal dosing of 600 mg/m 2 2 times a day, maximum of 1 g 2 times a day), 73 azathioprine (2 mg/kg/d to 3 mg/kg/d), 78 and rituximab (dosed as noted in table 6-2 ), 74,75 and a small case series supports the use of tocilizumab (8 mg/kg every 4 weeks, maximum of 800 mg per dose) 79 . The author typically avoids azathioprine in children given its higher risk of intolerable side effects.…”
Section: Relapsing Demyelinating Syndromesmentioning
confidence: 93%
“…When the area postrema is involved, hiccups and/or intractable vomiting may be part of the initial manifestations 18 . Given that the diencephalon can be affected, more than half of all children with NMOSD may exhibit evidence of endocrinopathies, including hyponatremia, morbid obesity, amenorrhea, and hyperinsulinism 74 . Pediatric NMOSD can coexist with systemic autoimmune disorders, such as systemic lupus erythematosus, Sjögren syndrome, and Graves disease.…”
Section: Relapsing Demyelinating Syndromesmentioning
confidence: 99%
“…viewed all previously reported studies of hyponatremia in patients with AQP4 antibody-positive/negative NMOSDs via a search of PubMed between 2005 and 2017 [3][4][5][6][7][8][9][10][11][12][13][14][15][16]. We obtained 14 studies that had reported on 28 patients with AQP4 antibodies-positive (n = 27)/ negative (n = 1) NMOSDs with hyponatremia, including 10 case reports and 4 retrospective studies.Table 1presents clinical and laboratory characteristics of the studies.…”
mentioning
confidence: 99%
“…Time course of serum sodium levels and urine volumesEstablishing an accurate diagnosis is particularly important because the treatment for each condition is quite different.To discuss the diagnosis and pathophysiological mechanisms underlying various types of hyponatremia in NMOSDs, we reviewed all previously reported studies of hyponatremia in patients with AQP4 antibody-positive/negative NMOSDs via a search of PubMed between 2005 and 2017 [3][4][5][6][7][8][9][10][11][12][13][14][15][16]. We obtained 14 studies that In our two patients, hyponatremia developed at the initial or early stage of their first attack.…”
mentioning
confidence: 99%